Preliminary validation of a mobile force Sensing device for clinical and telerehabilitation. (18th September 2020) - Bechard, Laura; Bell, Kevin; Lynch, Andrew
Abstract: Muscle strength and force production are important measures of patient progress during physical rehabilitation. Reliable and objective measurements are important to ascertain throughout rehabilitation. Current methods—manual muscle testing, electromechanical dynamometer, and hand-held dynamometer—are accurate and reliable, but have limitations that prevent wide implementation. As healthcare systems adapt to more patient-centered outcome models, changes to the delivery of rehabilitation, whether at-home or in the clinic, must also change to become more cost effective and accessible and provide quantifiable information regarding patient progress. We developed a novel Force Sensing (FoSe) device to quantify either tensile or compressive isometric muscle strength. The device was tested in a laboratory setting with healthy participants (n = 32) and compared to the commonly used hand-held dynamometer (HHD). Participants used both devices to perform several common isometric muscle tests including: hip abduction, knee extension, knee flexion, shoulder external rotation, and shoulder internal rotation. Compared to the HHD, FoSe was found to be an accurate and reliable measurement of force production. Intraclass Correlation Coefficients ranged from 0.58 to 0.89 without a magnitude dependent variation in force measurement. A second round of clinical testing with a patient population is warranted to determine FoSe's ability to measure clinically relevant asymmetry and progress over time. Further usability testing also needs to be conducted to determine the adequacy of FoSe for at-home use by both patients and clinicians.